2018
DOI: 10.1016/j.jpeds.2018.06.051
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Childhood Experiences, Epigenetic Measures, and Obesity in Youth

Abstract: This study lays the groundwork for future longitudinal studies to elucidate these mechanisms further and identify novel interventions to alleviate the health burdens associated with early adversity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 58 publications
1
25
0
Order By: Relevance
“…Lynch et al . examined data from the 2011–2012 National Survey of Children’s Health and found that exposure to two or more adverse family experiences (AFEs) was associated with higher odds of overweight and obese status [ 25 ]. Heerman et al reported a similar result utilizing the 2011–2012 National Survey of Children’s Health.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Lynch et al . examined data from the 2011–2012 National Survey of Children’s Health and found that exposure to two or more adverse family experiences (AFEs) was associated with higher odds of overweight and obese status [ 25 ]. Heerman et al reported a similar result utilizing the 2011–2012 National Survey of Children’s Health.…”
Section: Discussionmentioning
confidence: 99%
“…They found that children who had more AFEs were also at higher risk for overweight or obesity status [26]. Furthermore, Lynch et al found that exposure to certain childhood experiences, death of a parent and hardship due to family income, were stronger predictors of childhood obesity than other adverse experiences [25]. Isohookana et al observed that female adolescents who had experienced adverse childhood events were more likely to be obese and engage in unhealthy weight control behaviors [27].…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…Research from high-income countries suggests that a range of traumatic events (TEs) including abuse, neglect, and exposure to or experience of violence are important determinants of physical and mental health in later life (Kaufman et al, 2018;Riem & Karreman, 2019;Wiehn et al, 2018). Trauma in childhood is thought to have direct effects on cognitive development, inflammation, and stress hormones, leading to poor cardiovascular and cardiometabolic outcomes and higher rates of depression and anxiety (Danese et al, 2009;Danese & McEwen, 2012;Suglia et al, 2018;Tosevski & Milovancevic, 2006).…”
Section: Introductionmentioning
confidence: 99%